Ulcerative Colitis and Its Association with Salmonella Species - Tripathi, Manish Kumar; Pratap, Chandra Bhan; Dixit, Vinod K.; Singh, Tej Bali; Shukla, Sunit K.; Jain, Ashok K.; Nath, Gopal (Interdisciplinary Perspectives on Infectious Diseases, 2016)
Ulcerative colitis (UC) is characterized by presence of ulcer in colon and bloody diarrhea. The present study explores the possibility of association between Salmonella and ulcerative colitis. The present study comprised 59 cases of UC, 28 of colon cancer (CC), 127 of irritable bowel syndrome (IBS), and 190 of healthy control. The serological study was done by Widal and Indirect Haemagglutination Assay (IHA) for ViAb. Nested PCR was performed targeting fliC, staA, and stkG gene for Typhi and Paratyphi A, respectively. A total of 15.3% patients were positive for Salmonella “O” antigen among them 18.6% UC, 35.5% CC, 12.6% IBS, and 15.3% healthy control. A total of 36.9% patients were positive for “H” antigen including 39.0%, 57.1%, and 67.7% UC, CC, and IBS, respectively. About 1.73% show positive agglutination for AH antigen including 3.4%, 3.6%, and 1.6%, UC, CC, and IBS. A total of 10.89% were positive for ViAb. While 6.8% of UC, 10.7% of CC, 11.0% of IBS, and 12.1% of healthy subjects were positive for the antibody, the PCR positivity rates for Salmonella specific sequences were 79.7% in UC, 53.6% in CC, 66.1% in IBS, and 16.3% in healthy controls. The present study suggested that higher prevalence of Salmonella might play important role in etiopathogenesis of UC, IBS, and CC.